"We are all so different that it is just … normal." Normalization practices in an academic hospital in the Netherlands. Issue 2 (June 2018) - Leyerzapf, Hannah; Verdonk, Petra; Ghorashi, Halleh; Abma, Tineke A.
Highlights: Normalization practices in an academic hospital explain away diversity issues. Professionalism-as-neutral and equality-as-sameness norms enable normalization. Normalization justifies a hierarchical ordering of difference/sameness. Majority and minority enact an ideal worker norm producing privilege/disadvantage. Inclusion requires acknowledging power dynamics and unsettling normalization. Abstract: Internationally, academic hospitals are giving increasing attention to diversity management. This paper sheds light on the actual praxis of cultural diversity management by professionals in workplace interactions. An ethnographic study in a Dutch academic hospital showed that normalization practices were obscuring diversity issues and obstructing inclusion of cultural minority professionals. The normalization of professionalism-as-neutral and equality-as-sameness informed the unequal distribution of privilege and disadvantage among professionals and left no room to question this distribution. Majority and minority professionals disciplined themselves and each other in (re)producing an ideal worker norm, essentialized difference and sameness, and explained away the structural hierarchy involved. To create space for cultural diversity in healthcare organizations in the Netherlands and beyond, we need to challenge normalization practices.